Prophylactic Extended-Field Irradiation in Patients With Cervical Cancer: A Literature Review - Wang, Weiping; Zhou, Yuncan; Wang, Dunhuang; Hu, Ke; Zhang, Fuquan (Frontiers in Oncology, 2020)
Currently, the standard radiation field for locally advanced cervical cancer patients without evidence of para-aortic lymph node (PALN) metastasis is the pelvis. Due to the low accuracy of imaging in the diagnosis of PALN metastasis and the high incidence of PALN failure after pelvic radiotherapy, prophylactic pelvic and para-aortic irradiation, also called extended-field irradiation (EFI), is performed for patients with cervical cancer. In the era of concurrent chemoradiotherapy, randomized controlled trials are limited, and whether patients with cervical cancer can benefit from prophylactic EFI is still controversial. With conformal or intensity-modulated radiation therapy, patients tolerate prophylactic EFI very well. The severe toxicities of prophylactic EFI are not significantly higher than those of pelvic radiotherapy. We recommend delivering prophylactic EFI to cervical cancer patients with common iliac lymph nodes metastasis. Clinical trials are needed to investigate whether patients with ≥ 3 positive pelvic lymph nodes and FIGO stage IIIB disease can benefit from prophylactic EFI. According to the distribution of PALNs, it is reasonable to use the renal vein as the upper border of the radiation therapy field for patients treated with prophylactic EFI. The clinical target volume expansion of the node from the vessel should be smaller in the right para-caval region than in the left lateral para-aortic region. The right para-caval region above L2 or L3 may be omitted from the PALN target volume to reduce the dose to the duodenum. More clinical trials on prophylactic EFI in cervical cancer are needed.